Healthcare workers' views on decentralized primary health care management in Lesotho: a qualitative study - Ermyas Birru; Melino Ndayizigiye; George Wanje; Tholoana Marole; Patrick D. Smith; Masebeo Koto; Ryan McBain; Lisa R. Hirschhorn; Mathabang Mokoena; Annie Michaelis; Joel Curtain; Emily Dally; et al. (BMC, 2024)
Abstract Background Lesotho experienced high rates of maternal (566/100,000 live births) and under-five mortality (72.9/1000 live births). A 2013 national assessment found centralized healthcare management in Ministry of Health led to fragmented, ineffective district health team management. Launched in 2014 through collaboration between the Ministry of Health and Partners In Health, Lesotho's Primary Health Care Reform (LPHCR) aimed to improve service quality and quantity by decentralizing healthcare management to the district level. We conducted a qualitative study to explore health workers' perceptions regarding the effectiveness of LPHCR in enhancing the primary health care system. Methods We conducted 21 semi-structured key informant interviews (KII) with healthcare workers and Ministry of Health officials purposively sampled from various levels of Lesotho's health system, including the central Ministry of Health, district health management teams, health centers, and community health worker programs in four pilot districts of the LPHCR initiative. The World Health Organization's health systems building blocks framework was used to guide data collection and analysis. Interviews assessed health care workers' perspectives on the impact of the LPHCR initiative on the six-health system building blocks: service delivery, health information systems, access to essential medicines, health workforce, financing, and leadership/governance. Data were analyzed using directed content analysis. Results Participants described benefits of decentralization, including improved efficiency in service delivery, enhanced accountability and responsiveness, increased community participation, improved data availability, and better resource allocation. Participants highlighted how the reform resulted in more efficient procurement and distribution processes and increased recognition and status in part due to the empowerment of district health management teams. However, participants also identified limited decentralization of financial decision-making and encountered barriers to successful implementation, such as staff shortages, inadequate management of the village health worker program, and a lack of clear communication regarding autonomy in utilizing and mobilizing donor funds. Conclusion Our study findings indicate that the implementation of decentralized primary health care management in Lesotho was associated a positive impact on health system building blocks related to primary health care. However, it is crucial to address the implementation challenges identified by healthcare workers to optimize the benefits of decentralized healthcare management.